DAYA SAING USAHA TANI PADI DI KECAMATAN SUSUKAN KABUPATEN SEMARANG MENGGUNAKAN METODE PAM (POLICY ANALYSIS MATRIX) - Yoanes Krisostomos Nargy Justra Septaris; Tinjung Mary Prihtanti (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2019)
Competitiveness requires a country to excel in competitive and comparative advantage. The commodities that need to be developed are rice. This commodity was chosen because it is a commodity that the government prioritizes and is full of agricultural policies. The purpose of this study is to determine profits, competitive and comparative advantages and the impact of government policies. This research was conducted in March 2018 in Susukan District, Semarang Regency. The sampling technique used purposive sampling technique with a total of 30 respondents. Data analysis using Policy Analysis Matrix (PAM). The results showed that farming has a competitive and comparative advantage seen from the value of PCR and DRCR less than 1 but the DRCR value of 0.935 means that farming is feared no longer has comparative advantage if there is no interference from government policy. For the government, the policy of subsidizing fertilizers and pesticides is continued so that the farming business remains competitive but the use of fertilizer by farmers should be reduced so that it is in accordance with recommendations from the Agriculture Service or researchers. Marketers should target the domestic market because the price of rice in the international market is lower than in the country.